ON THE MIOCENE CENTRACANTHIDAE (TELEOSTEI, PERCIFORMES) FROM THE EASTERN PARATETHYS - Bannikov A.F. (My University, 2006)
A new genus, Naslavcea, is erected for the Middle Miocene species Spicara fundata Bannikov, 1990 (Centracanthidae) from the Lower Sarmatian of northern Moldova. This genus is characterized by the relatively small number of rays in the dorsal and anal fins. At the same time, Pelates islamdagicus Prokofiev, 2001 from the Lower Miocene of the Apsheron Peninsula (Azerbaijan) is transferred from the family Terapontidae to Centracanthidae and referred to the genus Spicara. © Pleiades Publishing, Inc. 2006.
Keywords: CENTRACANTHIDAE; EASTERN PARATETHYS; MIOCENE; NEW TAXA; PERCIFORMES; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен